The Existence of Kotagede's Specialty Foods as Yogyakarta's Traditional Culinary Heritage - Satria Krisna Aji; Yusuf Anwar Arya Putra; Dio Saputra; Emi Tipuk Lestari (Gastronomy and Culinary Art, 2026)
This study aims to examine the existence of Kotagede's traditional foods as part of Yogyakarta's culinary heritage and their role in preserving local cultural identity amid the tide of modernization. The research method used is a qualitative descriptive approach through field observations, in-depth interviews with culinary business actors, and a literature review related to gastronomy and culture. The results of the study show that Kotagede's traditional foods, such as kipo, legomoro, and geplak, not only have economic value as culinary products, but also carry historical and symbolic values that reflect the local wisdom of the community. The existence of these culinary traditions is increasingly preserved through the role of the community, support from the local government, and promotion through cultural tourism. However, challenges remain in the form of changing tastes among the younger generation, competition from modern foods, and limited regeneration of traditional culinary producers. Thus, the preservation of Kotagede's traditional foods requires a collaborative strategy between the community, business actors, and the government to ensure that this culinary heritage remains relevant and sustainable.